Natural Disasters and Economic Growth in Indonesia - Idroes, Ghalieb Mutig; Hardi, Irsan; Nasir, Muhammad; Gunawan, Eddy; Maulidar, Putri; Maulana, Ar Razy Ridha (Heca Sentra Analitika, 2023)
Natural disasters can have a profound impact on a country's economic growth, making it crucial for policymakers to understand the relationship between natural disasters and economic growth in order to develop effective strategies that mitigate adverse effects and promote sustainable development. The study utilizes secondary data spanning from 1990 to 2021 and employs the Fully-Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), Canonical Co-Integrating Regression (CCR), and Vector Error Correction Model (VECM) methods. The study's findings provide valuable insights into the substantial effects of natural disasters on economic growth, indicating a positive long-term impact. Furthermore, the analysis highlights a unidirectional causality, illustrating the notable influence of natural disasters on the country's economic performance. Policymakers should prioritize investments in upgrading and retrofitting infrastructure, focusing on key sectors like transportation, energy, water, and telecommunications, to mitigate the adverse effects of natural disasters and promote sustainable economic growth.